Exogenous-oxidant-free electrochemical oxidative C–H phosphonylation with hydrogen evolution. Issue 29 (22nd March 2019) - Yuan, Yong; Qiao, Jin; Cao, Yangmin; Tang, Jingmei; Wang, Mengqin; Ke, Guojuan; Lu, Yichen; Liu, Xue; Lei, Aiwen
Abstract : We herein report a versatile and environmentally friendly electrochemical oxidative C–H phosphonylation protocol. Abstract : We herein report a versatile and environmentally friendly electrochemical oxidative C–H phosphonylation protocol. This protocol features a broad substrate scope; not only C(sp 2 )–H phosphonylation, but also C(sp 3 )–H phosphonylation is tolerated well under exogenous-oxidant-free and metal catalyst-free electrochemical oxidation conditions.